Prevalence of increases in functional connectivity in visual, somatosensory and language areas in congenital blindness - Heine, Lizette; Bahri, Mohamed Ali; Cavaliere, Carlo; Soddu, Andrea; Laureys, Steven; Ptito, Maurice; Kupers, ron (Frontiers in Neuroanatomy, 2015)
There is ample evidence that congenitally blind individuals rely more strongly on non-visual information compared to sighted controls when interacting with the outside world. Although brain imaging studies indicate that congenitally blind individuals recruit occipital areas when performing various non-visual and cognitive tasks, it remains unclear through which pathways this is accomplished. To address this question, we compared resting state functional connectivity in a group of congenital blind and matched sighted control subjects. We used a seed-based analysis with a priori specified regions-of-interest (ROIs) within visual, somato-sensory, auditory and language areas. Between-group comparisons revealed increased functional connectivity within both the ventral and the dorsal visual streams in blind participants, whereas connectivity between the two streams was reduced. In addition, our data revealed stronger functional connectivity in blind participants between the visual ROIs and areas implicated in language and tactile (Braille) processing such as the inferior frontal gyrus (Broca's area), thalamus, supramarginal gyrus and cerebellum. The observed group differences underscore the extent of the cross-modal reorganization in the brain and the supra-modal function of the occipital cortex in congenitally blind individuals.